Cardiopulmonary arrest in primary care clinics: more holes than cheese: a survey of the knowledge and attitudes of primary care physicians regarding resuscitation - Sharon Einav; Oren Wacht; Nechama Kaufman; Eliezer Alkalay (Israel Journal of Health Policy Research, 2017)
Abstract Background Patients experiencing pre-arrest symptoms may first refer to their primary care physician. The study's aim was to determine the likelihood that a patient undergoing out-of-hospital cardiac arrest will receive appropriate resuscitation efforts in a primary care clinic in a country with a directive that clinics maintain resuscitation equipment and physicians undergo periodic resuscitation training. Methods An anonymous, 23-question online cross-sectional survey was created and administered to primary care physicians working in community clinics (10/1/2015-5/3/2015). Recruitment was accomplished by posting a link to the survey to all physicians listed as registered Society of Family Medicine members and in other online forums dedicated to residents and board-certified specialists in family medicine in Israel. The primary outcome measure was the proportion of respondents whose responses indicate that they fulfill all conditions for performing resuscitation. Results Of approximately 2400 potential respondents, 185 replied to the survey; the study's findings should be viewed as preliminary. Respondents' characteristics were generally similar to those of the study population, but respondents had a higher rate of family medicine specialists. Respondents were mostly female (n = 108, 58%) Israeli graduates who have practiced medicine for > 10 years (72%, n = 134). 55% (n = 101) had undergone basic life support (BLS) training within < 2 years. Although just 5% (n = 10) estimated call-to-Emergency Medical Service (EMS) arrival time to their clinic to be <5 min, only 64% (n = 119) knew the telephone number for summoning EMS. Most confirmed the existence of a resuscitation cart in their clinic (85%, n = 157); 68% confirmed the presence of a defibrillator (n = 126). Most respondents were aware of the location of the defibrillator in their clinic (67%, n = 123), stated its accessibility during working hours (63%, n = 116), and 56% (n = 103) knew how to use it. Only 28% of the questionnaires indicated that all requirements for mounting an effective BLS response had been fulfilled. Conclusions The study suggests that many primary care clinics are under-equipped and their physicians are under-prepared to initiate life-saving services. Steps must be taken to rectify this situation. In addition, to develop more reliable estimates of the phenomena reported in this preliminary study, these issues should be re-examined in the context of a high response rate physician survey.